PERLINDUNGAN INVESTOR DI PASAR MODAL INDONESIA: ANALISIS NORMATIF TERHADAP PERAN REGULASI DAN OTORITAS JASA KEUANGAN - William Christopher Yang; Gunardi Lie (PT. Hasba Edukasi Mandiri, 2025)
The capital market serves as an important instrument for companies to obtain funding. On the other hand, investors are often in a weaker position due to limited access to information and the high risk of market misconduct. This condition creates a strong need for clear legal protection. This study focuses on two main issues, namely the legal framework governing investor protection in Indonesia and the role of the Financial Services Authority (OJK) in carrying out its supervisory function. The research applies a normative juridical approach by examining relevant laws, regulations, and literature. The findings show that although existing regulations, such as the Capital Market Law and the OJK Law, provide a foundation for investor protection, challenges remain in their implementation. Weaknesses are found in supervisory practices and in the low level of financial literacy among the public. Therefore, strengthening regulations and optimizing the supervisory role of OJK are necessary to ensure more effective investor protection in the Indonesian capital market.